Effect of Ni/Fe ratio on microstructure, tensile flow and work hardening behaviour of tungsten heavy alloys in heat treated and swaged conditions. Issue 2 (17th January 2021) - Panchal, Ashutosh; Venugopal Reddy, K.; Azeem, P. A.; Sarkar, Rajdeep; Paradkar, Archana; Nandy, T. K.; Singh, A. K.
ABSTRACT: The present work describes the effect of Ni/Fe ratio on microstructure, tensile flow and work hardening behaviour of tungsten heavy alloys (WHAs) based on 92 wt. % W with varying Ni/Fe ratios in heat treated and swaged conditions. Evaluation of properties in the heat treated and swaged conditions reflect that the increasing Ni/Fe ratio has resulted in the enhancement of tensile as well as impact properties. Quantitative metallography and fractography have been conducted to identify the role of microstructural attributes on the failure behaviour in both the tensile and impact energy tests. The properties improvements at higher Ni/Fe ratios are due to the realisation of microstructure comprising relatively higher dissolved W in the matrix phase, higher volume fraction of matrix and reduced contiguity of W particles. True stress–true plastic strain curves of present alloys on log–log scale display two- and single-slopes in heat treated and swaged conditions, respectively. The instantaneous work hardening curves reveal the presence of three distinctive regimes (I, II and III) in heat treated and swaged conditions. The second derivatives of true stress–true plastic strain curves are parabola.